Opieka zdrowotna i promocja zdrowia w Rzeszowie. Kontekst opieki medycznej i zachowań zdrowotnych mieszkańców Rzeszowa - Błaszczuk, Katarzyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
Issues related to health of individuals and populations are classified among the phenomena occurring in social environment which require interdisciplinary approach. In course of our relations and contacts with others, we develop our health-related habits and we assume the roles of either healthy or sick or disabled person. Maintenance of good health makes it possible for people to accomplish life goals, develop their intellectual potential, achieve happiness, and gain satisfaction linked with their specific social roles. The study reviews statistical data related to various preventive healthcare services in the city of Rzeszow, acquired from reports published by Health Department of the Podkarpackie Marshal Office, Social Policy Department at the Podkarpackie Province Office and Health Department at the Municipal Office of Rzeszow. Issues related to health promotion have been discussed taking into account data of Health Department at the Municipal Office of Rzeszow and data derived from reports of entities coordinating the Network of Health Promoting Schools. The presented analysis of issues related to health of Rzeszow residents covers the period from 2004 to 2013.
Keywords: healthcare; prevention; health promotion